Negative electron affinity of adamantane on Cu(111). - Li, Jieru; Niesner, Daniel; Fauster, Thomas (Journal of Physics: Condensed Matter, 2021)
Photoelectron spectroscopy is used to show that thick adamantane films on Cu(111) have a negative electron affinity of -0.3 ± 0.1 eV. The ionization potential is obtained as 8.55 ± 0.15 eV resulting in a band gap of 8.9 ± 0.1 eV. For films of about 1.4 monolayer thickness the electron affinity is close to zero and the valence bands are shifted toward the Fermi energy due to charge transfer from Cu 3d bands.